TRANSLATION METHODS OF PHRASAL VERBS IN SUBTITLES OF THE COCO MOVIE - Arie Wijayanto; Evert Hilman (IKIP Siliwangi, 2023)
This study aimed to find out the type of phrasal verb and translation methods used by translators in translating phrasal verb in subtitles of the Coco movie. This study is based on chesterman's theory from